Blogi w dyskursie korporacyjnym: język, rola i funkcje - Fronczak, Katarzyna (Języki specjalistyczne w komunikacji interkulturowej, 2020)
The subject of this paper is the presentation of corporate blogs as a new form of corporate communication, their linguistic and discursive characteristics and the role they perform in corporate communication. The analyses of corporate blogs combine corpus linguistics methodologies (McEnery, Wilson 1996) and discourse analysis (Partington, Duguid, Taylor 2013) with the use of corpus tools, such as computational programs „Wmatrix4” (Rayson 2008) and „Word Smith 4.0” (Scott 1996), necessary to conduct quantitative analyses. The research material constitutes a corpus of English-language corporate blogs, compiled by the author, which consists of 500 randomly selected corporate blog posts taken from the corporate blogs run by ten top corporations from the field of Business Process Outsourcing and Information Technology. The study is the first attempt at a systematic and detailed linguistic description of corporate blogs. The results show that corporate blogs are unique texts due to their hybrid nature. In addition, it has been demonstrated that they fulfil promotional, persuasive as well as advisory and informative functions. Also, corporate blogs are used to reinforce corporate culture, corporate identity and corporate image. As a result, the authors of corporate blogs provide their readers with the impression of a more personal type of communication, which departs from a typical business model, as well as attract and persuade them to maintain and strengthen the business relationship. The results of the study provided an up-to-date, systematic and detailed description of the language used in corporate blogs, their role and functions in corporate discourse as well as their generic status.